Qualitative changes in urban structures. the degraded wetland recovery in the metropolitan area of the greater resistencia, argentina (2010)
The present article aims to reflect the existing complex interaction between the processes of urban sprawls and their impact on natural environments and to analyze, in particular, the experiences in the Gran Resistencia (province of the Chaco, Argentine Republic). It rescues the study case as a background, interprets it in terms of the theory of the complexity, allowing evaluation of the incidence of catastrophes such as floods, viewed like “a constructive and positive” process that has allowed the introduction of changes necessary to protect the population from such situations and to improve the natural environment management. The process has made possible a change in the perception of the population, having improved the coexistence with its context, and inducing the authorities to take measures to restore natural environments degraded in the sprawl process, creating policies to include them like recreational spaces. These river and lagoons areas are part of a complex system of wetlands designated as Ramsar sites. Its progressive incorporation to the recreational park, contributes to heighten the quality of life of its inhabitants.